2021
DOI: 10.1002/cssc.202101323
|View full text |Cite
|
Sign up to set email alerts
|

AZ31 Magnesium Alloy Foils as Thin Anodes for Rechargeable Magnesium Batteries

Abstract: prototypes comprising ultrathin AZ31 Mg alloy anodes ( � 25 μm thick) and Mg x Mo 6 S 8 Chevrel-phase cathodes exhibited cycling performance equal to that of similar cells containing thicker pure Mg foil anodes. The possibility of using ultrathin processable Mg metal anodes is an important step in the realization of rechargeable Mg batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 24 publications
2
37
0
Order By: Relevance
“…AZ31 alloy, consisting of 96 % Mg, 3 % Al, and 1 % Zn by weight, is a representative anode in magnesium battery applications, and it possesses remarkable formability and acceptable electrochemical properties. [8,[21][22][23] Noked et al recently reported that the electrochemical characteristics of AZ31 alloy anodes are comparable to those of commercially available 100 μm thick magnesium metal foils. [8] The warm-rolled magnesium foil prepared in this work exhibited superior magnesium dissolution-deposition performance, in terms of both overpotential and Coulombic efficiency, to the AZ31 alloy anode, although relatively stable magnesium dissolution-deposition cycling was achieved using this alloy (Figure S2).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…AZ31 alloy, consisting of 96 % Mg, 3 % Al, and 1 % Zn by weight, is a representative anode in magnesium battery applications, and it possesses remarkable formability and acceptable electrochemical properties. [8,[21][22][23] Noked et al recently reported that the electrochemical characteristics of AZ31 alloy anodes are comparable to those of commercially available 100 μm thick magnesium metal foils. [8] The warm-rolled magnesium foil prepared in this work exhibited superior magnesium dissolution-deposition performance, in terms of both overpotential and Coulombic efficiency, to the AZ31 alloy anode, although relatively stable magnesium dissolution-deposition cycling was achieved using this alloy (Figure S2).…”
Section: Resultsmentioning
confidence: 91%
“…[8,[21][22][23] Noked et al recently reported that the electrochemical characteristics of AZ31 alloy anodes are comparable to those of commercially available 100 μm thick magnesium metal foils. [8] The warm-rolled magnesium foil prepared in this work exhibited superior magnesium dissolution-deposition performance, in terms of both overpotential and Coulombic efficiency, to the AZ31 alloy anode, although relatively stable magnesium dissolution-deposition cycling was achieved using this alloy (Figure S2). The cycling profiles of the symmetric cell further support the better electrochemical performance of the cold-rolled magnesium foil, reaching over 200 cycles with an overpotential of < 80 mV after the 10 initial cycles of the activation processes, whereas a short circuit occurred in AZ31 (Figure 2e).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Maddegalla et al have proposed to replace the pure Mg foil by an ultrathin (ca. 25 μm of thickness) foil of Mg-alloy (3% Al and 1% Zn), and they concluded that the ultrathin Mg-alloy is much better than the pure Mf foil [ 97 ].…”
Section: Low-voltage Electrodementioning
confidence: 99%